Realidad aumentada con base en fotografía y video sobre el Danzante de Pujilí. - Cajamarca Jácome, Félix David (2020)
The purpose of the audiovisual proposal was to implement an alternative means for cultural dissemination on the main character of the traditional celebration of Corpus Christi, "The Dancer" from Pujilí canton. The project was aimed at visitors and tourists from Pujilí canton, aged between 15 years and up. It should be mentioned that the visitor has the need to know several of the representative characteristics of the Dancer such as: the historical background, symbolic concept, clothing, dance, and musical rhythm. Data that were investigated and used as informative concepts in the development of the proposal. The objective of this project was to design an audiovisual product applying augmented reality based on photography and video about the dancer from Pujili. Taking into account a previous analysis of augmented reality as a means of cultural dissemination. For this reason, it was possible to define that Artivive is the appropriate application related to its final presentation. On the other hand, the project contains research techniques: bibliographic, documentary and field, in order to obtain reliable and secure information. In addition surveys to visitors from other provinces and residents of Pujilí and, interviews with experts on the culture related to the dancer for a valid guide were conducted, also to specialists in the field of multimedia, audiovisual production and photography. Once the appropriate research was carried out, the appropriate methodology to define the product concept was determined, so Dario Saeed´s multimedia projects methodology was taken into account, which consists of six phases that allowed the construction of multimedia product and its diffusion presented photographs printed in postal size. Generating a cultural and informative value, linked to the new technologies available to each person.